Thermal packaging for advanced timing device in space - Jocelyn, Elizabeth (2017)
The Chip Scale Atomic Clock (CSAC) would allow small and portable electrical devices to have their own accurate timing device. However, the stability of CSAC has to be evaluated for various conditions and in this case, the area of application of interest is for space applications. The aim of this project is thus to develop a suitable thermal package to protect a CSAC from extreme space thermal environment. Given the small range of operating temperature of CSAC and the limitations of a CubeSat, it is crucial to develop a thermal control solution that is compact and requires little to no power consumption. In order to develop the thermal packaging, various available thermal control solutions are considered. The most suitable one would be used and designed to suit the CSAC’s application. In-depth analysis was also done to quantify the effectiveness of the thermal packaging. This includes simulation with ANSYS Thermal followed by fabrication and testing. The Multi-Layer Insulation (MLI) was chosen out of all the other thermal control solutions as it is lightweight and require no moving parts, hence it will not consume the limited power of the CubeSat. Orbital analysis was also done to find out the range of temperatures that the CSAC would be exposed to while in orbit, so that the simulation and experimental parameters can be set as close to actual conditions. In conclusion, the simulations and experimental results prove that the thermal packaging using MLI is effective in maintaining CSAC’s temperatures to be between its operating temperatures.